Memahami Perkembangan Jiwa Keagamaan Pada Anak Dan Remaja - Ratna Wati (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The main issues discussed in this study was to understand the development of religious life in children and adolescents, according to Zakiyah Darajat that religious life in children and adolescents had been developed in line with the development of their physical and psychological. While in the context of the education of children and adolescents, parents and educators must understand and recognize how well the religious development in children and adolescents. The purpose of this research was to find scientific theories which are concrete and valid related to religion on mental development in children and adolescents. This research is a libarary research with descriptive qualitative using the Analysis Contain Approach, which analyzes the theories from the up to date and authentic sources. The research result found that: the stage of religious development in children through three stages, namely; (1) The Fairly Tale Stage (Fables Level); (2) The Realistic Stage (Confidence); and (3) The Individual Stage (Individual Level). The factors that influence are: (1) The Education of the family; (2) Educational institutions; (3) The education of the society. The development of the religious life in adolescence was strongly influenced by the development of their psychological aspects, namely mental and mind growth, social considerations, emotional development, moral development, attitudes and interests which also affected by other factors such as; internal factors (heredity, age, psychiatric dissorders, and personality) and external (family, institutional, and community).